Grouting in the ground proceedings of the conference organized by the Institution of Civil Engineers and held in London on 25-26 November 1992 - Bell, A. L. (Thomas Telford, 1994)
This title provides an opportunity for engineers to catch up with trends in geotechnical grouting and provides an in-depth discussion of the advances, views and knowledge from around the world. Topics range from compensation grouting, jet grouting soil mixing and permeation grouting to ten monitoring and more.